2016
DOI: 10.1039/c5cp06999h
|View full text |Cite
|
Sign up to set email alerts
|

Production of renewable fuels by the photohydrogenation of CO2: effect of the Cu species loaded onto TiO2 photocatalysts

Abstract: The efficient gas phase photocatalytic hydrogenation of CO2 into a desirable renewable fuel was achieved using a Cu-loaded TiO2 photocatalyst system. Enhancing the amount of Ti(3+) relative to Ti(4+) in a Cu-loaded TiO2 photocatalyst provided an excellent opportunity to promote the photohydrogenation of CO2. The coexistence of Cu and Cu(+) species during the photoreaction was shown to efficiently enhance the photocatalytic activity by prolonging the lifetime of the electrons. To achieve the best photoactivity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 42 publications
0
34
0
Order By: Relevance
“…Chen et al recently reported CO 2 6 hydrogenation to maximum 28.72 μmol g -1 methane over Cu modified TiO 2 under UV-C irradiation. They showed presence of Cu and Cu + species and ratio of Ti +3 with respect to Ti +4 enhances the photoactivity [21]. Tan et al have prepared copper nanoparticles decorated TiO 2 nanorod films using electrochemical method for reduction of CO 2 to methane (2.91 ppm g -1 h -1 catalyst) [22].…”
Section: Introductionmentioning
confidence: 98%
“…Chen et al recently reported CO 2 6 hydrogenation to maximum 28.72 μmol g -1 methane over Cu modified TiO 2 under UV-C irradiation. They showed presence of Cu and Cu + species and ratio of Ti +3 with respect to Ti +4 enhances the photoactivity [21]. Tan et al have prepared copper nanoparticles decorated TiO 2 nanorod films using electrochemical method for reduction of CO 2 to methane (2.91 ppm g -1 h -1 catalyst) [22].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Cu/TiO 2 catalyst was reported to be effective for photocatalytic CO 2 reduction, in which the Cu + and Cu 0 species formed by H 2 ‐reduction was confirmed to be more active in charge separation than Cu + species alone . Cu/TiO 2 was also used in the photocatalytic hydrogenation of CO 2 into CH 4 and the coexistence of Cu 0 and Cu + was beneficial to enhance the activity by prolonging the lifetime of electrons …”
Section: Introductionmentioning
confidence: 99%
“…[19] Cu/ TiO 2 was also used in the photocatalytic hydrogenation of CO 2 into CH 4 and the coexistence of Cu 0 and Cu + was beneficial to enhance the activity by prolonging the lifetime of electrons. [20] Considering the above-mentioned results, we have investigated the feasibility of Cu catalyst for direct N-methylation of N-methylaniline (MA) with CO 2 and H 2 . In the present work, TiO 2 (P25) was employed as a support to disperse Cu species and Cu/TiO 2 samples were prepared by deposition-precipitation method and tested for the target reaction in n-octane.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, higher photoactivity could be seen over Cu/TiO 2 monolithic photocatalyst for CO production. Recently, similar observations have been reported for photocatalytic CO 2 reduction to CO and CH 4 over Cu/TiO 2 photocatalyst in a gas phase system [43].…”
Section: Photocatalytic Co 2 Reduction With Hmentioning
confidence: 59%